Fungsi Notaris dalam Pembuatan Akta Fidusia Terkait Perkara yang Diselesaikan melalui Restorative Justice - Fiorentina Fiorentina; Achmad Faishal (Lembaga Yasin AlSys, 2026)
Although restorative justice (RJ) has been adopted in criminal law enforcement in Indonesia, the resulting settlement agreements often lack executorial force, leaving victims in legal uncertainty. This study aims to analyze the legal position of the Fiduciary Deed in supporting the RJ Settlement Deed and to construct an ideal legal framework for synchronizing the two deeds. This study used a normative legal method with statutory and conceptual approaches. Legal materials were collected through library research and analyzed prescriptively using the deductive method. The results show that the Fiduciary Deed, as an accessory agreement, fundamentally transforms the victim’s position from complainant to preferred creditor, converts the promise of compensation into a security right in rem, and provides executorial force equivalent to a court decision. Following Constitutional Court Decision No. 18/PUU-XVII/2019, notaries play a strategic role in formulating adaptive default clauses. This study also identifies three integration models, with the Notarial Settlement Deed model as the model with the strongest legal force. The conclusion of this study emphasizes the importance of the Fiduciary Deed as a legal instrument that provides executorial power to settlement agreements in RJ, so that the objective of victim recovery can be realized more certainly and quickly. The implications of this study include recommendations for amending the Fiduciary Security Law, revising Perpol No. 8/2021, issuing a Joint Regulation, and opening new professional and economic spaces for notaries.